Extemporaneous Compounding Practice for Dermatologic Preparations in Ethiopian Public Hospitals: Regulatory Requirements and Quality Concerns - Selam, Muluken Nigatu (Risk Manag Healthc Policy, 2021)
Extemporaneous compounding is among the key hospital pharmacy services that promotes pharmaceutical care. It is a long-standing practice in dermatology for patients who need custom-made drug products. The practice of dermatologic compounding practice in Ethiopian public hospitals is found at the beginning and very few hospitals have started the practice so far. This research communication aimed at examining Ethiopian public hospitals’ extemporaneous compounding practice for dermatologicals with emphasis on regulatory requirement and quality control activities. To benefit patients from these products, good compounding practice should be obeyed in line with the expansion of the service. Gaps have been observed in the facilities with regard to quality assurance system and compliance with the country’s regulatory requirements. This implies a need to take appropriate and timely actions by the responsible stakeholders and expand the service in the country by fulfilling the regulatory requirement.